One pot microwave-assisted synthesis of 2,5-dimethylfuran from bamboo hydrolysate in presence of green solvent and low-cost metal catalyst - Lim, Huei Yeong; Rashidi, Nor Adilla; Yusup, Suzana (Center of Biomass & Renewable Energy (CBIORE), 2025)
This study looked at the one-pot synthesis of 2,5-dimethylfuran (DMF) from glucose-rich bamboo hydrolysate using microwave heating technology in presence of green solvent, Low Transition Temperature Mixture (LTTM), and activated carbon-supported copper catalyst (Cu/AC). While DMF is mainly synthesized by using commercial glucose, the biomass with high cellulose content can also be used. Besides, the conventional synthesis that commonly employs organic solvents and noble metal catalysts has great toxicological and financial barriers. Thus, alternative cheaper and greener solvents and catalysts are needed, such as LTTM and carbon-supported copper. The bamboo hydrolysate was produced via acid hydrolysis with 0.5M sulphuric acid (H2SO4). LTTM was synthesized using choline chloride (ChCl) and malic acid, which were proven to be effective in DMF production in presence of H2SO4. Reaction time, catalyst loading, and LTTM ratio were studied via response surface methodology with DMF yield as the response. Temperature was set at 120 °C in accordance with previous study. The LTTM was found to experience minimal mass loss at this reaction temperature. The Cu/AC catalyst was found to carry mostly reduced copper oxide (CuO) particles, with slight CuO residues, indicating successful synthesis of the catalyst. A quadratic regression model has been developed with R2=0.9481, with expected optimal condition at 1 min reaction time, 1% catalyst loading, and 4:1 LTTM ratio, with expected DMF yield of 25.61 mol% (13.67 mass percent). Experimental validation yielded 21.28 ± 0.77 mol% (11.36 mass percent), indicating that this regression model was accurate. Overall, this study shown that the LTTM and Cu/AC are capable of producing DMF from biomass in one-pot manner.